Declining levels of serum chemokine (C‐X‐C motif) ligand 10 over time are associated with new onset of psoriatic arthritis in patients with psoriasis: a new biomarker?. (1st November 2020) - Abji, F.; Lee, K.‐A.; Pollock, R.A.; Machhar, R.; Cook, R.J.; Chandran, V.; Gladman, D.D.
Summary: Background: We previously found that serum levels of chemokine (C‐X‐C motif) ligand 10 (CXCL10) decreased after the onset of psoriatic arthritis (PsA). Objectives: We measured CXCL10 levels over time in patients with psoriasis who developed PsA to determine whether the drop in CXCL10 was specific to these patients and further assess its association with PsA development. Methods: Prospectively followed patients with psoriasis without arthritis [cutaneous psoriasis (PsC)] were assessed yearly by rheumatologists for the presence of PsA. Patients with PsC who developed PsA (converters) were matched to those that did not develop PsA (nonconverters) based on psoriasis duration and the interval between follow‐up visits. The duration between baseline and the first visit postconversion in converters was used to assign a pseudoconversion date in nonconverters. Linear mixed‐effects models were used to model the expression of CXCL10 over time. Results: CXCL10 significantly declined over time in converters prior to PsA development with a significant difference in the trend over time between converters ( n = 29) and nonconverters ( n = 52; P < 0·001). CXCL10 continued to decline after PsA onset in a subset of converters. There was a significant difference in the trend of CXCL10 levels between converters ( n = 24) and nonconverters ( n = 16; P = 0·01) preconversion/pseudoconversion. This difference remained postconversion ( P = 0·006) and was not different from the preconversion period ( P = 0·75). Conclusions: A large difference in CXCL10 was identified in patients with PsC that are destined to develop PsA over time. This exploratory analysis supports the association of CXCL10 with PsA development in patients with PsC and warrants further study of the predictive ability of this chemokine. What is already known about this topic? Chemokine (C‐X‐C motif) ligand 10 (CXCL10) is elevated in psoriatic affected tissues and serum and/or plasma. Patients with psoriasis that develop psoriatic arthritis (PsA) have elevated CXCL10 levels at baseline and these levels drop after arthritis onset. What does this study add? By monitoring levels of CXCL10 in serum over multiple visits in patients with psoriasis that develop PsA as well as those that do not develop PsA, an association was identified between CXCL10 and PsA development. What is the translational message? CXCL10 is a strong candidate for use by physicians for the detection of patients with psoriasis that are at risk of developing PsA. Linked Comment: Kirby and Fitzgerald. Br J Dermatol 2020; 183 :805–806 .